EFFICACY OF PUBOVAGINAL SLING USING FASCIA LATA FOR TREATMENT OF URODYNAMIC STRESS INCONTINENCE IN FEMALES: Effects of Pubovaginal Sling - Alia, Asma; Ahmed, Faizan; Burney, Muhammad Rehan (Pakistan Armed Forces Medical Journal, 2009)
Objective: To evaluate results of pubovaginal sling surgery for the treatment of urodynamic stress incontinence in females. Study Design:  Descriptive study. Place and Duration of Study:  This study was carried out in Pakistan Naval Services Shifa, Karachi & Armed Forces Institute of Urology,Rawalpindi from February 1997 to February 2004. Patients and Methods: Thirty two Pubovaginal sling operations using fascia lata were performed at Pakistan Naval Ship Shifa, Karachi and Armed Forces Institute of Urology, Rawalpindi in females having severe urodynamic stress incontinence. The inclusion criteria was women with stable bladder, having post void residual urine (PVRU)